2017
DOI: 10.1017/s0007114517000848
|View full text |Cite
|
Sign up to set email alerts
|

Faster eating rates are associated with higher energy intakes during anad libitummeal, higher BMI and greater adiposity among 4·5-year-old children: results from the Growing Up in Singapore Towards Healthy Outcomes (GUSTO) cohort

Abstract: Faster eating rates are associated with increased energy intake, but little is known about the relationship between children's eating rate, food intake and adiposity. We examined whether children who eat faster consume more energy and whether this is associated with higher weight status and adiposity. We hypothesised that eating rate mediates the relationship between child weight and ad libitum energy intake. Children (n 386) from the Growing Up in Singapore Towards Healthy Outcomes cohort participated in a vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
81
1
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 102 publications
(94 citation statements)
references
References 79 publications
(91 reference statements)
8
81
1
4
Order By: Relevance
“…Similar findings have been reported in studies conducted with children [4][5][6][7][8][9]. We have recently demonstrated that children who ate at a faster rate consumed on average 75% more energy compared to children who ate slower [10]. A better understanding of the specific behaviours through which these faster eating rates are achieved will inform intervention strategies to support weight management and help reduce excessive early childhood weight gain.…”
supporting
confidence: 82%
See 3 more Smart Citations
“…Similar findings have been reported in studies conducted with children [4][5][6][7][8][9]. We have recently demonstrated that children who ate at a faster rate consumed on average 75% more energy compared to children who ate slower [10]. A better understanding of the specific behaviours through which these faster eating rates are achieved will inform intervention strategies to support weight management and help reduce excessive early childhood weight gain.…”
supporting
confidence: 82%
“…Among children whose BMI was in the overweight range, all children had higher levels of SAT. As reported previously, children with overweight tended to eat at a faster rate (g/min) than healthy weight children [10]. Subsequent analysis of specific differences in eating microstructure showed that faster eating rates among children with overweight and among children with higher abdominal adiposity were attributable to larger bite size.…”
Section: Comparison Of Eating Microstructure Among Children With Healsupporting
confidence: 68%
See 2 more Smart Citations
“…Example behaviors that have been studied include slowing eating rate [29, 30], chewing food more slowly [31], reducing visible portion size [1], and controlling bite size [26]. Many of these eating behaviors, including eating rate, bite size, and time each bite spends in the oral cavity, are inter-related [9, 10, 21]. …”
Section: Introductionmentioning
confidence: 99%